The Effects of Board Characteristics on Corporate Social Responsibility Disclosure - Mohd Redzuan, Zulkiflee (2012)
This paper examines the effect of corporate governance characteristics (board composition and ownership structure) on the extent of disclosure in their annual report on corporate social responsibility activities concerning community, environment, employees and products among non-financial listed companies in Malaysia based on top 100 market capitalization. Nowadays, there is a tremendous demands by stakeholders to the companies in demonstrate greater transparency on their activities. Many studies have been conducted in Malaysia on the area of voluntary disclosure on corporate social responsibility. The current study aimed to evaluate the current level of corporate social responsibility disclosure (CSRD) and investigate the effects of the corporate governance variables, board composition (board size, board independence and board qualification) and ownership structure (CEO ownership and non-executive ownership) and control variable (firm size) in relationship to the level of CSRD in 2010 in 74 top 100 based on market capitalization companies listed on the Bursa Malaysia. The results indicates that the corporate governance variables are influencing the level of information disclosed, thus confirming the hypotheses. The results showed that the level of corporate social responsibility disclosure (CSRD) level was acceptable compared to other studies. With regard to the quality of disclosure, the results on the corporate governance characteristics (board composition and ownership structure) showed that there are positive and negative relationship between CSRD and corporate governance variables. The variable that is positively linked to CSRD is board size, board independence; board qualification, family ownership and Malay director ownership and the negative linked relationship are board cross directorship, CEO ownership and non-executive ownership. However the result on control variable is negatively associated with CSRD.